The COVID-19 Pandemic and Tokyo Olympic Games postponement: Athlete resilience and mental Health - Rogers, M. C. (University of Calgary, 2021)
The COVID-19 global pandemic, at the time of writing this thesis, is creating unprecedented challenges globally. In the world of high-performance sport, as a result of the pandemic, the Tokyo 2020 summer Olympic Games were postponed for one year. Nevertheless, the pandemic, combined with the Olympic postponement, provides a unique opportunity to study athlete experiences using the construct of psychological resilience, which has been associated with performance success and positive mental health outcomes and is defined as an individual`s ability to adapt positively to adversity (Fletcher & Sarkar, 2013). The purpose of this research was to explore the experiences of Canadian athletes preparing for the Tokyo summer Olympic Games during the COVID-19 global pandemic. Semi-structured interviews were conducted with 20 Canadian athletes who were training for the Olympic games in both individual and team sports. Athletes spoke of how they experienced and managed the pandemic and developed resilience, and their stories highlight the complex nature of managing adversity. In the narrative manuscript, the stories from eight participants are presented to illustrate four narrative types: the critical role of context, the essential nature of social support, the importance of developing multiple identities and being more than an athlete, and the relevance of deeply reflecting on one`s life. An athlete`s personal context, such as Olympic qualification, stage of their career, physical and mental health, and access to resources influenced how they lived their narrative, highlighting the importance of considering both individual and environmental factors in relation to resilience. Current research highlights that the development of resilience can support an athlete`s mental health and the results from the narrative manuscript in this thesis underscore the importance of a high-performance sport environment that not only provides strong social support but is also structured to nurture athlete mental health. Therefore, the second paper builds on this notion of a high-performance sport environment that is psychologically safe and mentally healthy by creating a working definition of a mentally healthy high-performance sport environment and outlining how the sport psychology practitioner can support the coach, athlete, and support staff in ensuring such an environment.